Identifying geochemical hot moments and their controls on a contaminated river floodplain system using wavelet and entropy approaches. (November 2016) - Arora, Bhavna; Dwivedi, Dipankar; Hubbard, Susan S.; Steefel, Carl I.; Williams, Kenneth H.
Abstract: Geochemical hot moments are defined here as short periods of time that are associated with disproportionally high levels of concentrations (biogeochemically-driven or transport-related) relative to longer intervening time periods. We used entropy and wavelet techniques to identify temporal variability in geochemical constituents and their controls along three transects within a contaminated floodplain system near Rifle CO. Results indicated that transport-dominated hot moments drove overall geochemical processing in the contaminated groundwater and seep zones. These hot moments were associated with seasonal hydrologic variability (∼4 months) in the contaminated aquifer and with annual hydrologic cycle and residence times in the seep zone. Hot moments associated with a naturally reduced zone within the aquifer were found to be biogeochemically-driven, with a different dominant frequency (∼3 months) and no correlation to hydrologic or weather variations, in contrast to what is observed in other regions of the floodplain. Highlights: We interrogated complex, multivariate geochemical datasets to identify hot moments in a floodplain environment. We introduced a novel wavelet-entropy approach to classify hot moments and their distribution. Geochemical hot moments were found to be primarily transport-related/hydrologically-driven at the site. Within a naturally reduced zone, hot moments were dominated by lithologic characteristics (biogeochemically-driven). Water quality managers can use this wavelet-entropy tool for identifying contaminant hot moments in other floodplain settings.